Pola Asuh Makan dan Status Gizi Balita di Wilayah Kerja Puskesmas Simpang Kawat - Putri, Nora Amelia; Zein, Zafrullah; Wulansari, Arnati; Merita, Merita; Fatmawati, Tina Yuli (Prosiding Seminar Kesehatan Nasional, 2023)
Toddlers is an important period in the process of growth and development. At this time there is a rapid increase so that it is called the golden period in the life cycle. To achieve this, of course, it is influenced by two important aspects, namely the parenting feeding provided by parents and also the nutritional status of the toddler. This research is a quantitative study with a cross sectional design. The population in this study were toddlers in the Simpang Kawat Health Center working area, totaling 2237 toddlers. The sample used was 94 respondents with a proportional random sampling technique. The data analysis technique used is the Chi Square test. It is known that from 94 respondents, 78 people (83%) respondents have a good toddler eating feeding. 94 respondents, 79 people (84%) respondents have good nutritional status. There is a relationship between parenting feeding (p-value: 0.000) Â with the nutritional status of toddlers in the Simpang Kawat Health Center, Jambi City. It is expected that parents, especially mothers, can pay attention to parenting feeding in toddlers so that the nutritional status of toddlers is always good